Occupational Safety and Health Implications of the 2022 Gas Pipeline Eruption at Federal College of Education (Technical), Omoku - Nwogbidi, Kingsley Chibuzor; Nwogbidi, Susan Ibuzoraknu; Peter, Eze Ojadi; Tew, Beauty Chinyere (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Occupational Safety and Health (OSH) in a work environment is focused on protecting worker’s safety and health in the context of physical, mental and social wellbeing. This paper presents some occupational health and safety hazards associated with Federal College of Education (Technical) Omoku Campus II work environment consequent upon a gas leakage that occurred in 2022. An in-situ measurements of the levels of gases and volatile organic compounds was carried out using standard well calibrated instruments and equipment, the results indicate that the mean levels in parts per million (PPM) of the measured gas parameters at the Campus II work environment were higher than other sites and above regulatory limits, there were perceived impacts of bad air quality which were of major concern. The paper concludes with recommendations to all relevant authorities on the need for a proper OHS management system for all community’s affect